David Matto and his contribution on clinical pathology and psychiatrics in Peru - Álvarez-Carrasco, Ricardo Iván (2020)
Doctor David Matto-Usandivaras made important contributions in Peruvian medicine, particularly in clinical pathology and psychiatrics, at the end of 19th and at the beginning of the 20th century, coinciding with the scientificist thoughts that became prevalent in the years after the war between Peru and Chile. Nonetheless, time passed by and his contributions became forgotten, so the purpose of this paper is to rescue Dr. Matto-Usandivaras contributions and place them in a proper context so members of the Peruvian medical community – particularly pathologists and psychiatrists – may become more knowledgeable of his valuable work.